Biosensors in Health Care: The Milestones Achieved in Their Development towards Lab-on-Chip-Analysis - Suprava Patel; Rachita Nanda; Sibasish Sahoo; Eli Mohapatra (Biochemistry Research International)
Immense potentiality of biosensors in medical diagnostics has driven scientists in evolution of biosensor technologies and innovating newer tools in time. The cornerstone of the popularity of biosensors in sensing wide range of biomolecules in medical diagnostics is due to their simplicity in operation, higher sensitivity, ability to perform multiplex analysis, and capability to be integrated with different function by the same chip. There remains a huge challenge to meet the demands of performance and yield to its simplicity and affordability. Ultimate goal stands for providing point-of-care testing facility to the remote areas worldwide, particularly the developing countries. It entails continuous development in technology towards multiplexing ability, fabrication, and miniaturization of biosensor devices so that they can provide lab-on-chip-analysis systems to the community.